Stent occlusion in endoscopic ultrasound-guided gallbladder drainage from bleeding mitigated by double pigtail plastic stent deployment within lumen apposing metal stent - Murali Dharan (Society of Gastrointestinal Intervention, 2021)
Double pigtail plastic stents (DPTPS) are routinely placed with the lumen apposing metal stent (LAMS) during endoscopic ultrasound-guided gall bladder drainage. Several reasons are postulated for this practice. This case report highlights a previously unreported benefit from use of DPTPS within LAMS.